Utilizing the Lotto Wabena Game to Foster Cognitive Development in Young Children - Aprilia, Rizka; Heldanita, Heldanita; Novita, Yulia; Purnama Sari, Wardani; Salina Samaun, Siti; Murniati, Wahyuni; Irawan, Yossy (Nak-Kanak: Journal of Child Research, 2025)
Background of the study: This research is motivated by the lack of variety in the use of educational games as engaging learning media for early childhood. Conventional methods are still widely used and often fail to optimally support cognitive development in young learners. Therefore, it is necessary to introduce innovative game-based tools that can enhance children's thinking abilities in a playful and developmentally appropriate way. One such tool is the Lotto Wabena game, designed to stimulate children's memory, attention, categorization, and logical reasoning. Aims and scope of paper: The aim of this study is to develop the Lotto Wabena game as a learning medium to improve cognitive development in children aged 5–6 years. The research is limited to learners at Al Husnayaini Kindergarten, Kubang Raya District, Pekanbaru, and focuses on the tool’s feasibility, quality, and effectiveness. Methods: This is a research and development (R&D) study using the Borg and Gall model. Data were collected through observation, interviews, documentation, and questionnaires. Validation was conducted by content and media experts. The data, mainly qualitative, were analyzed using assessment criteria to evaluate the developed game. Results: Material expert validation showed a score of 87.5% (very feasible), while media expert validation reached 91.62%. Cognitive improvement was evident, with pre-test scores averaging 46.63% and post-test scores reaching 91.35%. A small group trial yielded a score of 94.28%, indicating a strong positive impact on cognitive development. Contribution: This study provides a validated, effective game-based learning tool that supports cognitive growth in early childhood and offers practical implications for educators and curriculum developers.